PEMBERANTASAN TINDAK PIDANA PENYELUNDUPAN BENIH LOBSTER DI KOTA BATAM - Padrisan Jamba; Zuhdi Arman (Semarang Law Review (SLR), 2025)
The crime of lobster seed smuggling is of great concern to the public and the government, because this crime occurs very often, and its consequences are detrimental to the state. Although the catching and releasing of lobster seeds is no longer allowed and strictly regulated, and the perpetrators will be punished, these activities are still widespread. The purpose of this study was to identify legal policies, barriers and efforts to eradicate the crime of smuggling lobster seeds in Batam City. Empirical legal research is used as a research method. The result of the study is that the legal policy regarding the criminal activities of lobster smuggling in Batam City, as a law enforcer, has been consistent in order to always enforce the law in accordance with the mandate of the Law of the Republic of Indonesia. Public awareness, which is still low, may become an obstacle to the enforcement process. This can be seen in the reluctance of the population to file reports or be witnesses to the emergence of a law enforcement process. Law enforcement efforts include Preemptive Efforts (Foresight), Preemptive Efforts (Prevention), and Repressive Efforts. It is hoped that the legal policy for crimes related to smuggling should be regulated more specifically in order to create a deterrent effect on criminals.   Abstrak Tindak pidana penyelundupan benih lobster menjadi perhatian besar bagi pemerintah dan masyarakat, karena sangat sering tindak pidana ini terjadi dan akibatnya merugikan negara. Meski penangkapan dan pelepasan benih lobster tidak lagi diperbolehkan dan diatur secara ketat, serta pelakunya akan dihukum, namun masih maraknya kegiatan tersebut dilakukan. Tujuan dari penelitian ini adalah untuk mengidentifikasi kebijakan hukum, hambatan dan upaya pemberantasan tindak pidana penyelundupan benih lobster di Kota Batam. Penelitian hukum empiris digunakan sebagai metode penelitian. Hasil penelitian adalah bahwa kebijakan hukum mengenai tindak pidana penyelundupan lobster di Kota Batam sebagai penegak hukum telah konsisten untuk selalu menegakkan hukum sesuai dengan amanat Undang-Undang Republik Indonesia. Kesadaran masyarakat yang masih rendah dapat menjadi kendala dalam proses penegakan hukum. Hal ini terlihat dari keengganan masyarakat untuk melapor atau menjadi saksi munculnya proses penegakan hukum. Upaya penegakan hukum meliputi Upaya Preemtif (Peninjauan ke Depan), Upaya Preventif (Pencegahan), dan Upaya Represif. Kebijakan hukum terhadap kejahatan yang berkaitan dengan penyelundupan diharapkan dapat diatur lebih spesifik supaya membuat efek jera terhadap pelaku kejahatan.